Application of radio ground-wave propagation theory to the tomographic imaging of ground surfaces. - Zhipeng Wu (IEEE Transactions on antennas and propagation)
Radiowave propagation over ground has been historically studied for predicting the radiated fields when the ground properties are known and the field has been well covered over the past hundred years. The theory of ground-wave propagation is applied to the inverse problem of the tomographic imaging of ground surfaces. After the inverse problem is formulated, an iterative technique for solving it is illustrated. This is based on the minimization of the cost function of the measured and estimated scattered fields produced by the surface under investigation in isolation. Numerical simulation results are presented for the reconstruction of four different ground features surrounded by sea water namely: (1) dry ground; (2) wet ground; (3) dry-wet mixed ground; and (4) dry ground with a central water pool. It has been demonstrated that the technique is able to reconstruct the distributions of normalized surface impedance of the isolated surfaces and, hence, their images. The iterative process can converge with a small number of iterations using the normalized surface impedance of sea water as the initial guessed values. However, better images can be produced using a priori information. This study thus illustrates a new application of ground wave propagation theory with possible applications in ground surface mapping, remote sensing, target positioning and monitoring, and navigation